An innovative surgical approach: suture fixation of the levonorgestrel-releasing intrauterine system in the treatment of adenomyosis - Huizhi Zhang; BenBen Cao; Jinyi Tong; Jialu Guo; Jianfeng Zheng; Linling Zhu; Zheng Niu; Li Chen (BMC, 2022)
Abstract Background Placement of a levonorgestrel-releasing intrauterine system (LNG-IUS) is an effective treatment for adenomyosis, especially for patients who have severe dysmenorrhea symptoms but a strong desire to preserve fertility. Nonetheless, for patients with adenomyosis accompanied by an enlarged uterus, expulsion of the ring is a troublesome problem. In this study, we sewed and fixed the LNG-IUS in the uterus, which provides a good solution to this problem. Methods In this prospective case series approved by the Ethics Committee of Hangzhou Women's Hospital, 12 patients with adenomyosis were successfully enrolled after providing informed consent, and all patients underwent long-term postoperative follow-up. Results Twelve patients with adenomyosis underwent suture fixation with an LNG-IUS, and during the long-term postoperative follow-up, every patient experienced complete remission of their symptoms: a significant decrease in menstrual flow, relief of dysmenorrhea, and improvement in quality of life. Only one person reported expulsion a year later. Conclusion In patients with adenomyosis suffering from dysmenorrhea or excessive menstrual blood loss, suture fixation of an LNG-IUS using the hysteroscopic cold knife surgery system is a minimally invasive and effective alternative treatment for adenomyosis and decreases the risk of LNG-IUS expulsion.